Asian Paints:Changing Rules of the Game - Singhi, Rushina; Kawale, Dewyani; Chaudhari, Yogesh (Indian Journal of Marketing, 2009)
The present case study deals with the distribution and supply chain management of Asian Paints. The case study tries to throw light on the key strategies of Asian Paints in terms of distribution and supply chain, which have made Asian Paints, the number one paint company in India. The case study also focuses on the current scenario in the paint industry and the trends in the industry. The scope of case study is limited to the Indian paint market and the strategies applied by Asian Paints in the India market only.